Cancer Phytotherapy - Mahmood Bahmani PhD; Hedayatollah Shirzad PhD; Najmeh Shahinfard MSc; Laaleh Sheivandi MSc; Mahmoud Rafieian-Kopaei PhD (Journal of Evidence-Based Complementary & Alternative Medicine, 2017)
Nowadays, increases in resistance of tumors to the current therapeutic agents have become a problematic issue. Therefore, efforts to discover new anticancer compounds with high sensitivity of cancer cells are extending. Animal and laboratory researches have shown that exogenous antioxidants are able to help prevent the free radical damage associated with the development of cancer. However, researches in human beings have not demonstrated convincingly that taking antioxidants can reduce the risk of developing cancer. Angiogenesis is also a natural condition that controls the formation of new blood vessels from the available vessels. Today, it is believed that most of the cancers have angiogenesis potential and their growth, metastasis, and invasion depend on angiogenesis. Several compounds with plant origin and with anti-angiogenic properties have been identified. The aim of this study is to review recently published articles about anticancer drugs obtained from plants with antioxidant and anti-angiogenesis properties.